Copious relationships: transnational marriages and intimacy among Moroccan couples in Italy. Issue 4 (2nd October 2022) - Decimo, Francesca
ABSTRACT: This article aims to explore how intimacy is constructed and experienced among couples formed through transnational and arranged marriages, between Morocco and Italy. The analysis, conducted with a qualitative approach, begins by retracing the process of couple formation and the role that kinship plays in facilitating this transition in migrants' life courses. I then consider how love and intimacy are intertwined with the wider effort of family settlement in the Italian context. The investigation is developed in dialogue with the literature on the detraditionalization of intimacy, on one side, and transnational marriages, on the other. I argue that these couples achieve intimacy by pursuing copious relationships resulting from their ability to navigate among family extension and nuclearization, independence and reciprocal commitment, kin expectations and self-determination.